The Influence of Leadership and Work Discipline on Employee Performance with Work Motivation as a Mediator - kholik, Nur; Wibowo, Sandi Nasrudin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Employee performance is a crucial factor in organizational success, especially in the manufacturing sector. This study aims to analyze the effect of leadership and work discipline on employee performance with work motivation as a mediator variable at PT. Dong Sheng Nusantara, Majalengka Regency. A quantitative approach with an explanatory design was used. A population of 135 employees was studied using a census method. Data were collected through a Likert scale questionnaire and analyzed using PLS-SEM. The results showed that leadership had a positive and significant effect on employee performance (β=0.352; t=4.125; p<0.01), work discipline had a positive and significant effect on employee performance (β=0.295; t=3.748; p<0.01), leadership has a positive and significant effect on work motivation (β=0.576; t=4.171; p<0.01), work discipline does not have a significant effect on work motivation (β=0.258; t=1.865; p>0.05), work motivation has a positive and significant effect on employee performance (β=0.258; t=2.964; p<0.01),. Work motivation significantly mediates the effect of leadership on employee performance (β=0.148; t=2.719; p<0.01). Work motivation does not mediate the effect of work discipline on employee performance (β=0.067; t=1.580; p>0.05). These findings imply that improving employee performance requires a structural approach through strengthening work discipline as well as a psychological approach through developing leadership that can motivate employees. Management is advised to strengthen leadership capacity, maintain a consistent disciplinary system, and design integrated motivation programs with leadership styles.